Autoimmune Encephalitis in Critical Care: Optimizing Immunosuppression - Rubin, Daniel B.; Batra, Ayush; Vodopivec, Ivana; Vaitkevicius, Henrikas (Seminars in Respiratory and Critical Care Medicine, 2017)
Autoimmune diseases affecting the nervous systems are a common cause of admission to the intensive care unit (ICU). Although there exist several well-described clinical syndromes, patients more commonly present with progressive neurologic dysfunction and laboratory and radiographic evidence of central nervous system (CNS) inflammation. In the critical care setting, the urgency to intervene to prevent permanent damage to the nervous system and secondary injury from the systemic manifestations of these syndromes often conflicts with diagnostic uncertainty. Furthermore, treatment is limited by current therapeutic agents that remain non-specific for individual diseases, especially for those whose pathophysiology remains unclear. Primary autoimmune, paraneoplastic, parainfectious, and iatrogenic neurologic disorders all share the common underlying pathophysiology of an adaptive immune response directed against an antigen within the nervous system. Several different mechanisms of immune dysfunction are responsible for pathogenesis within each of these categories of disease, and it is at this level of pathophysiology that the most effective and appropriate therapeutic decisions are made. In this review, we outline the basic diagnostic and therapeutic principles in the management of autoimmune diseases of the nervous system in the ICU. We approach these disorders not as lists of distinct clinical syndromes or molecular targets of autoimmunity but rather as clusters of syndromes based on these common underlying mechanisms of immune dysfunction. This approach emphasizes early intervention over precise diagnosis. As our understanding of the immune system continues to grow, this framework will allow for a more sophisticated approach to the management of patients with these complex, often devastating but frequently reversible, neurologic illnesses.
Keywords: autoimmune neurology; paraneoplastic disorder; limbic encephalitis; neurologic disorder